Interactive processes and learning attitudes in a web-based problem-based learning (PBL) platform. - Tseng, Kuo-Hung; Chiang, Feng Kuang; Hsu, Wen-Hua (Computers in Human Behavior, 2008)
This paper discusses the steps taken to set up a digital logic course problem through a problem-based learning (PBL) constructivist approach. PBL is the learning which results from the process of working toward the understanding and resolution of a problem. The purpose of this study was to develop and implement problem-based learning in a digital logic course in a senior vocational industrial high school. Data collection included content analysis and a questionnaire survey. Content analysis was used to evaluate the students' discussion messages, quality of dialogue, and the level of problem-solving activities. A survey was then administered to examine the students' learning attitudes and perceptions toward this platform as a possible tool for PBL learning. Researchers found “Peer-responses” category is the most messages; the contents of messages focus on “General explanation” and “Reaction”; the level results of all groups' problem-solving are similar; the index of the “Interaction” satisfaction level is the highest in PBL activity. Finally, some research suggestions were also proposed. Copyright (c) 2008 Elsevier Ltd.